Perancangan Mesin pengupas Kulit Telur Burung Puyuh Semi-Otomatis Berkapasitas 240 Butir / Jam - S, Rianto; Siregar, Amru; Tanjung, Faisal Amri (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2022)
The motivation behind this plan is to speed up the stripping of quail egg shells, quail eggs are typically handled with different types of food, subsequently requiring a stripping cycle. The timeframe for stripping quail egg shells by manual is a normal of 10 seconds/thing, on the off chance that in huge amounts a peeler is required. From these issues the creator made a "Self-loader Quail Egg Shell Peeler to Increase Productivity and Effectiveness in Quail Egg Shell Peeler". Shaft width. Estimation of creation limit depends on the revolution of the screwdriver with a heap. In light of the plan, the details of the device are gotten utilizing a 12 volt 62 rpm electric engine with a force of 300 watts, a shaft width of 20 mm. The creation limit is gotten by pivoting the screwdriver with a heap of 62 rpm with a creation limit of 240 grains.